High Radiation Burden of Minimally Invasive Approaches for Adult Spinal Deformity. (16th November 2020) - Godzik, Jakub; Mundis, Gregory M; Khan, Daniel; Merrill, Sarah; Mulholland, Celene B; Walker, Corey T; Turner, Jay D; Uribe, Juan; Eastlack, Robert
Abstract: INTRODUCTION: Minimally invasive spine surgery relies intraoperative fluoroscopy. As such, the subject of excessive radiation exposure to the patient and surgeon is of concern. METHODS: Patients with ASD from two institutions undergoing cMIS were identified using a prospectively collected database. Inclusion criteria were: coronal cobb (CC) ≥20°, pelvic incidence - lumbar lordosis (PI-LL) >10°, sagittal vertical axis (SVA) ≥5cm, pelvic tilt (PT) ≥25°, or thoracic kyphosis (TK) ≥60°, undergoing cMIS with more ≥3 intervertebral levels fused, and use of percutaneous screws. Fluoroscopy time and radiation emission (mGy) for all patients undergoing cMIS were retrospectively abstracted from the medical records; emission data were compared to risk thresholds based published by the US Nuclear Commission. RESULTS: 52 patients underwent cMIS deformity correction. Average age was 70±9 years, 41% were female with average BMI 29.4±5.4 and bone mineral density T-score of-1.6±0.8 (femur) and 1.4±0.6 (spine). Mean preoperative SVA was 9.1±12 cm, with preoperative PI-LL of 14±14°. On average, patients underwent a 5±1 level fusion, with 3±1 levels of lateral interbody fusion (LLIF); 40% of cases were revision operations. Mean total fluoroscopic time was 223±155 seconds, with mean radiation emission of 179±191 mGy (33-1038mGy); the average emission dose exceeded the annual risk threshold 36 times. Radiation dose did not appear to be associated with age (p = 0.81), number of levels (p = 0.37), number of LLIF's (p = 0.9), sagittal imbalance ( P = .09), and coronal imbalance ( P = .05). The greatest association was with spine T-score ( P = .004). CONCLUSION: Given the high doses of radiation exposure during MIS deformity correction, measures need to be taken to minimize exposure to the patient and surgeon. It is imperative that we consider and investigate strategies to reduce the radiation burden in the setting of treating deformity with minimally invasive techniques.